2015
DOI: 10.1590/0100-67622015000100012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro EVALUATION OF EUCALYPTUS ECTOMYCORRHIZAE ON SUBSTRATE WITH PHOSPHORUS DOSES FOR FUNGAL PRE-SELECTION

Abstract: -The benefit promoted by ectomycorrhizal depends on the interaction between symbionts and phosphorus (P) contents. Phosphorus effect on ectomycorrhizal formation and the effectiveness of these in promoting plant growth for fungal pre-selection were assessed under in vitro conditions. For P effect evaluation, Eucalyptus urophylla seedlings inoculated with four Pisolithus sp. isolates and others non-inoculated were grown on substrate containing 0.87, 1.16 and 1.72 mg P per plant. For evaluation of effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, concentrations above 3% resulted in signi cant viscosity, preventing the solution from forming beads properly. The most commonly used concentration is 2%, as observed in other studies involving the entrapment of ECM mycelia(Rodrigues et al 1999;Oliveira et al 2006;Repáč 2007;Rossi et al 2017;Costa et al 2019). In this study, 2% sodium alginate was the optimal concentration, providing the highest viability of A. odoratus mycelia and proper bead formation.…”
mentioning
confidence: 55%
“…On the other hand, concentrations above 3% resulted in signi cant viscosity, preventing the solution from forming beads properly. The most commonly used concentration is 2%, as observed in other studies involving the entrapment of ECM mycelia(Rodrigues et al 1999;Oliveira et al 2006;Repáč 2007;Rossi et al 2017;Costa et al 2019). In this study, 2% sodium alginate was the optimal concentration, providing the highest viability of A. odoratus mycelia and proper bead formation.…”
mentioning
confidence: 55%
“…The above-mentioned results suggested that diverse factors, such as ECM-fungus species or isolate, host species, and growth conditions, could influence plant Al tolerance following ECM inoculation. Bucking et al (40) suggested that mycorrhizae altered the host and fungus function, while Costa et al (41) observed that Pisolithus inoculation enhanced the growth of Eucalyptus urophylla. Overall, among the three tested ECM isolates, L. bicolor S238A was the most promising isolate, considering its capacity to confer Al tolerance in P. massoniana seedlings grown in an acidic yellow soil.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that Al resistance in ECM plants was affected by numerous factors, including ECM fungus species or isolates, host plant species, and growth conditions. Bucking et al [25] suggested that ectomycorrhizae could alter the function of both the host and fungus, while Costa et al [26] found that the growth of Eucalyptus urophylla benefited from an association with Pisolithus sp. Our results indicated that the symbiosis benefited the growth and function of both L. bicolor S238A and P. massoniana seedlings, but the underlying mechanisms need further study.…”
Section: Aluminum Resistance and Biomass Production In Ecm P Massonimentioning
confidence: 99%